High-resolution spatial analysis for the air quality regulation service from urban vegetation: A case study of Taipei City. (August 2022) - Chen, Han-Shi; Lin, Ying-Chen; Chiueh, Pei-Te
Highlights: PM2.5 emissions and regulation services data are spatialized in 30mx30m resolution. AERMOD and dry deposition model are integrated for measuring air quality in Taipei. The regulation services of five different types of urban vegetation are measured. Taipei citizens get limited benefits from the services provided by urban vegetation. The results may serve as a useful guideline for urban green infrastructure planning. Abstract: Rapid economic growth has caused air pollution, particularly in city areas. Removing air pollutants generated by various emission sources is crucial to control PM2.5, improve air quality, and maintain human health in high-density urban areas. In response to air pollution, urban vegetation plays an essential role in providing air quality regulation service. To estimate the air quality regulation service provided by urban vegetation, this study integrated spatial analysis, a dry deposition model, and an atmospheric diffusion model to spatially quantify the air quality regulation service of PM2.5 in Taipei City on a high-resolution scale (30  m  × 30 m per spatial unit). The results show that in 2016, total PM2.5 emissions in Taipei City were 1, 400.88 tonnes and that urban vegetation removed 18.31 tonnes of PM2.5, with an average PM2.5 removal rate of 0.16 g/m 2, and the corresponding PM2.5 concentration improvement value of 0.0136 μg/m 3 . This finding revealed a significant gap between the amounts of emissions and purifications of PM2.5, the air quality regulation service provided by the urban vegetation in Taipei City remains insufficient. The results of this study not only point out the spatial differences of regulation services and propose a new research framework for quantifying the natural benefits, but also as a guideline for governments to form the auxiliary policies of the urban ecosystem service and facilitate the urban green infrastructure planning. Graphical abstract: Image, graphical abstract